2017
DOI: 10.3928/00220124-20170321-10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Discrepancies in Perceived Nursing Competence Between Postgraduate-Year Nurses and Their Preceptors

Abstract: Preceptor development courses should be grounded in a strong pedagogical framework. An assessment tool with explicit behavioral indicators would be needed for objective evaluation from both perspectives. J Contin Educ Nurs. 2017;48(4):190-196.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…To understand better how different groups assess NGNs’ competence, three studies used comparative designs, with different findings. Chen, Chien, et al (2017) found no significant difference in overall competence assessment of NGNs compared with their preceptors. Numminen et al.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To understand better how different groups assess NGNs’ competence, three studies used comparative designs, with different findings. Chen, Chien, et al (2017) found no significant difference in overall competence assessment of NGNs compared with their preceptors. Numminen et al.…”
Section: Resultsmentioning
confidence: 97%
“…The Nurse Competence Scale (NCS) was the most used tool ( N = 10; Kuokkanen et al., 2016; Lima et al., 2016; Lima et al., 2014; Numminen et al., 2014; Numminen et al., 2015a; Numminen et al., 2015b; Numminen, Leino‐Kilpi, et al., 2016; Numminen et al., 2017; Numminen, Ruoppa, et al, 2016; Wangensteen et al., 2012). All other tools were used in four or less research papers each: Six‐Dimension Scale of Nurse Performance (6‐D Scale; Aggar, Bloomfield, Thomas, & Gordon, 2017; Aggar, Gordon, Thomas, Wadsworth, & Bloomfield, 2018), Modified Six‐Dimension Scale of Nurse Performance (M6‐D Scale; Bratt, Baernholdt, & Pruszynski, 2014), Holistic Nursing Competence Scale (HNCS; Jung et al., 2017; Takase et al., 2014), New Graduate Registered Nurse Transition Program Competency Tool (NGRNTPCT; Oblea et al., 2019), Nurse Competence Questionnaire (NCQ; Chen, Chen, Chen, Kuo, Li, & Chiang, 2017; Chen, Chien, et al, 2017), Nurse Professional Competence (NPC; Holowaychuk, 2018) and Overall Competency Tool/Specific Competency Tool (OCT/SCT; Blegen et al., 2015; Spector et al., 2015; Wilson et al., 2018; Woda et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] This is consistent with findings in medical and nursing students. 8,9 Additionally, top performers have been found to more accurately predict or evaluate their performance than bottom (third or fourth quartile) performers in studies of pharmacy and medical students, and underperformers tend to highly overestimate their knowledge and skills. 4,5,8 Findings in some studies suggest that while overall performance scores might be similar between instructor and learner, particular areas of rubrics tend to have larger discrepancies in scores.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, graduation plays a fundamental role in the development of nursing science, considering that the courses have objectives that converge to a broader and deeper education, which enables the production of qualified human resources, consolidating scientific knowledge to act in professional practice (13) . Thus, this study is justified in view of the need to summarize and discuss the content of academic production on the development of terminological subsets in order to provide a relevant research source to help choose the best strategies for structuring terminology subsets of CIPE ® , thus ensuring greater quality and reliability, as well as helping to conduct new studies.…”
mentioning
confidence: 99%